2022
DOI: 10.1007/s41999-022-00710-9
|View full text |Cite
|
Sign up to set email alerts
|

The association of care satisfaction and COVID-19 contact restrictions with quality of life in long-term care homes residents in Germany: a cross-sectional study

Abstract: Background Quality of life (QoL) is a widely recognised outcome in residents of long-term care homes. However, little is known about the impact of care satisfaction on QoL. The aim of this study was to assess the association between care satisfaction and QoL in residents of long-term care homes. Additionally, we were able to assess the impact of the Covid-19 contact restrictions on QoL. Methods We applied a cross-sectional study in N = 40 long-term care ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Although there are few studies about pandemic effects on palliative care in Germany [29][30][31][32][33][34][35] as well as pandemic effects on nursing homes in Germany [20,24,[36][37][38][39][40], at the time of article publication, no studies could be found on hospice and palliative care in German nursing homes under pandemic conditions. In particular, there are no studies in which the different perspectives of employees, residents and their relatives are combined.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are few studies about pandemic effects on palliative care in Germany [29][30][31][32][33][34][35] as well as pandemic effects on nursing homes in Germany [20,24,[36][37][38][39][40], at the time of article publication, no studies could be found on hospice and palliative care in German nursing homes under pandemic conditions. In particular, there are no studies in which the different perspectives of employees, residents and their relatives are combined.…”
Section: Introductionmentioning
confidence: 99%
“…13 Although these factors decrease a person's QoL, they do not directly assess QoL. Three small-scale cross-sectional studies [14][15][16] assessed NH residents' QoL directly during the COVID-19 pandemic, but none of them included the facilities' COVID-19 exposure or variables affected by COVID-19 exposure (eg, staff burnout) in their analyses. Another cross-sectional study 17 assessed the impact of COVID-19 on NH residents' QoL, using a COVID-19especific questionnaire (COV19eQoL 18 ).…”
mentioning
confidence: 99%